مقاصد القرآن في فكر بديع الزمان سعيد النورسي - Ziyad Khalil Mohammad Dagameen (TSAQAFAH, 2013)
Al-Qur’an is guidance for mankind, loaded with content and very comprehensive orientation. According to Said Nursi, though it’s words are limited, but actually the content of the meaning is no limits. The firmament capacity has very broad scope, covering various dimensions of life. In this article, before concluding Nursi’s perspective on maqāsid al-Qur’an, the writer sets forth some mufassir to compare and analyze the views of Nursi began from Fakhruddin al-Razi, al-Ghazali, al-Syatibi, Muhammad Abduh and Ibn Ashur. In the end, Nursi asserts there are at least four fundamental contents of al-Qur›an, that is monotheism, prophethood, resurrection and justice. The more admirable according to Nursi, four of this al-Qur›an contains are often found together in one sura, or together in a single verse (unity of the Qur›an). That is why, these four have a strong influence on al-Qur›an is I’jaz. And of the last four issues, the only one that can be proofed in human life is the justice, which includes not only in religious aspect of the shari’ah, but has a broad spectrum in human real life, begining from economic aspect, social, political, legal and other humanitarianism. In this point, moral values accentuate seemed very strong, as the basis of valuable and meaningful life, because the peak of morality is the principle of altruism, or khidmah to another person or party.